Narrative of the voyage of H.M.S. Herald during the years 1845-51, under the command of captain Henry Kellett, R.N., C.B.; being a circumnabigation of the globe, and three cruizes to the arctic regions in search of sir John Franklin (1853)
Esta publicación es una colección de historia natural, donde se describe por expertos naturalistas el lugar por donde pasaba la expedición: como Panamá, Río de Janeiro, Nueva Granada, Ecuador, Perú y otros.